Manajemen Kepala Madrasah dalam Meningkatkan Funsgi Guru dalam Proses Pembelajaran di MAS Al-Ihsaniyah Desa Sarang Burung Kab. Muaro Jambi Provinsi Jambi - Hamdi Hamdi (Journal of Social, Educational and Religious Studies, 2025)
The problem in this research is Headmaster‟s Management in improving the function of Teachers in MAS AL-Ihsaniyah Desa Sarang Burung. This study aims to find out how the principal formulates policies, regulates the work is procedures, supervises and the supporting factors and constrains the Principal in improving the function of teachers in MAS AL-Ihsaniyah Desa Sarang Burung. Methodologically, this research is field research (empirical) with qualitative approach. Primary data sources are principals, vice principals, administrative staff, teachers and students. While archival books, activity reports, and management implementation documents are secondary data. In data collection, the method used are observation, interview, and documentation. In analyzing data, the researcher used qualitative analysis techniques with the steps of data exposure, data reduction, and withdrawal conclusions. The general finding in this research is the objective condition of MAS AL-Ihsaniyah Desa Sarang Burung. The particular finding, is: (1) the formulation of Principal Policy in MAS AL-Ihsaniyah Desa Sarang Burung done by making planning, Implementation and evaluation through deliberations, discussions and forum meetings (2) Arrangement of the Working Procedures in MAS AL-Ihsaniyah Desa Sarang Burung done by dividing the task according to organizational structure. (3) Supervision of the principal in MAS AL-Ihsaniyah Desa Sarang Burung are conducted directly by monitoring all the students and teachers and monitoring to the classes. Indirectly, the principal conducts supervision through the vice principal of the curriculum section, student affairs, teachers of counseling guidance and picket teachers (4) Supporting factors in MAS AL-Ihsaniyah Desa Sarang Burung are infrastructure and cooperation with the Institute of Education. Inhibiting factors are limit the cost, time and energy, and the teachers have a less understanding about the policies that made by principal and reluctant to develop their potential.